A facile method to determine pore size distribution in porous scaffold by using image processing. (September 2015) - Lo Re, G.; Lopresti, F.; Petrucci, G.; Scaffaro, R.
Highlights: A new digital imaging procedure for pore size distribution analysis was developed. It accomplish a semi-automatic segmentation of images containing pores of any geometry. Colored maps of the porous structures are generated for analysis optimization. Abstract: Image processing permits scientists to investigate morphological properties of three-dimensional structures starting from their bi-dimensional gray-scale representation. In many cases porous structure with complex architecture has to be designed in order to attempt specific properties such in the case of scaffold for tissue engineering. Traditional morphological characterization, like scanning electron microscopy, should be coupled with quantitative information such as pore size distribution (PSD) in order to get a deeper understanding of the influence of the porous structure on tissue regeneration processes and on other related applications, it is remarkable to study a quantitative analysis of porosity and of pores dimension. In this work it was developed as a software able to accomplish the segmentation of images containing pores of any geometry in a semi-automatic way with the aim to measure the PSD. Case study constituted by PLA porous scaffolds with different pore size was adopted. Results indicate that image processing methods well fit the pore size features of PLA scaffolds, overcoming the limits of the more invasive porosimetry techniques.